2005
DOI: 10.1186/1475-2891-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal obesity and infant feeding-interactions

Abstract: Background: There are no data regarding the relationship between maternal adiposity and interaction and feeding of infants and possible contribution to childhood obesity. In this study we determined the relationship between maternal body weight and composition and infant feeding patterns and maternal-infant interaction during 24-hour metabolic rate measurements in the Enhanced Metabolic Testing Activity Chamber (EMTAC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Obese mothers are more likely to have postpartum depression [18]; depressed mothers are less likely to continue breastfeeding than non-depressed mothers [75]. A small study of obese formula-feeding mothers found that they spent less time interacting with infants over a 24 hour testing period than non-obese mothers [76]. …”
Section: Discussionmentioning
confidence: 99%
“…Obese mothers are more likely to have postpartum depression [18]; depressed mothers are less likely to continue breastfeeding than non-depressed mothers [75]. A small study of obese formula-feeding mothers found that they spent less time interacting with infants over a 24 hour testing period than non-obese mothers [76]. …”
Section: Discussionmentioning
confidence: 99%
“…Women with excessive GWG tended to be overweight or obese. In addition to a possible genetic influence, maternal overweight/obesity is associated with factors, such as feeding behaviours that may result in an obesogenic postnatal environment. Similarly, independent of maternal pre‐pregnancy BMI status, women with excessive GWG may also exhibit characteristics associated with an obesogenic postnatal environment .…”
Section: Discussionmentioning
confidence: 99%
“…Human epidemiologic data have also examined maternal obesity as a risk factor for food addiction in offspring. Five‐month‐old infants of obese mothers were demonstrated to have greater overall energy intake and increased drive to consume high‐carbohydrate foods compared with infants of normal‐weight mothers . A study that more directly examined the effect of maternal diet during pregnancy on offspring food intake and choice found an increased drive to overeat sweets in 1‐year‐old children of mothers who overconsumed sweet foods in pregnancy …”
Section: Maternal Obesity Is Associated With Neurodevelopmental and Pmentioning
confidence: 99%